Предмет: Математика,
автор: Leonardo27rus
(4х + 1) * (2х - 4) - 8х = 3 * (6 - х)
Ответы
Автор ответа:
0
(4х + 1) ·(2х - 4) - 8х = 3 · (6 - х)
8x²+2x-16x-4-8x=18-3x
8x²-19x-22=0
D=(-19)²-4·8·(-22)=1065
x₁=(19-√1065)/16 или x₂=(19+√1065)/16
8x²+2x-16x-4-8x=18-3x
8x²-19x-22=0
D=(-19)²-4·8·(-22)=1065
x₁=(19-√1065)/16 или x₂=(19+√1065)/16
Похожие вопросы
Предмет: Математика,
автор: upiterianin
Предмет: Алгебра,
автор: kristinka39057
Предмет: Английский язык,
автор: yuldashevdalbayb
Предмет: Физика,
автор: danyval